The reproduction of mothering: psychoanalysis and the sociology of gender - Chodorow, Nancy (University of California Press, 1978)
When this best-seller was published, it put the mother-daughter relationship and female psychology on the map. The Reproduction of Mothering was chosen by Contemporary Sociology as one of the ten most influential books of the past twenty-five years. With a new preface by the author, this updated edition is testament to the formative effect that Nancy Chodorow's work continues to exert on psychoanalysis, social science, and the humanities.
Keywords: 1900-1999; amériques; cours; cycles supérieurs; discipline; fem1000; fem9000; figure de la mère; genre; identités LGBTQIA2+; maternité; premier cycle; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; états-unis